The Role of Digital Media in Shaping Public Opinion And Political Participation - Nahria, Nahria; Tobo, Herdian; Nur, Muammar K.; Joumilena, Eveerth Z. (Indonesian Research Journal on Education, 2024)
The rapid evolution of digital media has transformed the dynamics of public communication, political engagement, and opinion formation in the 21st century. This study examines the role of digital media platforms such as social networks, online news portals, and digital discussion forums in shaping public opinion and influencing patterns of political participation. Using a mixed-methods approach that combines content analysis and survey-based data, the research explores how exposure to political information in digital environments affects citizens’ perceptions, attitudes, and willingness to participate in democratic processes. The findings reveal that digital media serve as both catalysts and filters of political discourse, enabling greater access to information while simultaneously reinforcing ideological polarization through algorithmic personalization. Moreover, the study identifies a strong correlation between the intensity of online engagement and the frequency of offline political activities, such as voting, protesting, and civic volunteering. However, the results also highlight the risks of misinformation, echo chambers, and superficial engagement driven by virality rather than critical reasoning. The study concludes that while digital media have expanded the democratic space by facilitating inclusivity and immediacy in political communication, they also necessitate strategic media literacy initiatives and regulatory frameworks to ensure the integrity of public discourse in the digital age.